Method for manufacturing neodymium alloy powder slurry and NdFeB sintered magnets
Patent Information
- Application Number
- JP2026051163
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-25
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167573000010 
Figure 2026167573000001 
Figure 2026167573000002
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a neodymium alloy powder slurry and a method for producing an NdFeB sintered magnet. BACKGROUND ART
[0002] NdFeB sintered magnets were invented by the present inventors in 1982 (see Patent Document 1), and not only far exceed the magnetic properties of previous permanent magnet materials, but also are inexpensive because they are mainly composed of resource-abundant raw materials such as neodymium (Nd: a type of rare earth element), iron and boron, and have steadily expanded their market as ideal permanent magnet materials. Their applications are diverse, including computer HDDs (Hard Disk Drives), magnetic head drive motors (VCM: Voice Coil Motors), high-end speakers, headphones, power-assisted bicycles, golf carts, and permanent magnet magnetic resonance diagnostic apparatuses (MRI). In recent years, furthermore, rapid practical implementation has been advancing in drive motors for hybrid cars and electric vehicles, energy-saving and low-noise large household appliances (air conditioners and refrigerators), elevators, and other industrial motors.
[0003] As methods for producing such NdFeB sintered magnets, a magnetic field in-die press method, a wet press molding method, an MIM (Metal Injection Molding) method, and the like are known. In the magnetic field in-die press method, magnet alloy powder is oriented in a die to which a magnetic field is applied, and is pressurized and compressed in the magnetic field (for example, 1.5 t / cm 2 ) to fix the oriented particles and form an oriented molded body, and the oriented molded body is sintered to produce a sintered magnet. However, due to the pressurization and compression, it was difficult to produce a highly oriented thin plate-shaped oriented molded body. Therefore, in this method, after a large bulk block-shaped magnet is fabricated, the block-shaped magnet is mechanically cut to form the final shape. However, machining causes deterioration of magnetic properties. In addition, a large amount of loss occurs during production, and there are problems such as poor yield. As shown in Patent Document 2, the wet press forming method involves injecting a slurry consisting of alloy powder and an oily solvent into a mold, applying a magnetic field orientation while discharging the oily solvent from the slurry by pressing to form an oriented molded body, and then sintering the oriented molded body to produce a sintered magnet. This wet press forming method also involves pressurized compression (for example, 1.0 t / cm²). 2 Because the oriented molded body is formed by ) ), it is difficult to manufacture thin, plate-shaped oriented molded bodies, similar to the magnetic field die pressing method, and the final shape is created by mechanically cutting from a large block of magnet. As a result, there are problems such as a large amount of loss during manufacturing and poor yield. Furthermore, Patent Document 2 states that when the proportion of oily solvent is small, it becomes almost entirely solid, worsening supplyability, and the orientation of the powder deteriorates during magnetic field molding. In other words, the slurry in Patent Document 2 has the alloy powder and oily solvent separated. The MIM method involves mixing alloy powder with a binder resin, heating the mixture to reduce its viscosity, and then injection molding it into a mold to form a filled molded body. After orienting the particles in a magnetic field, the binder is removed and the molded body is sintered. Because the MIM method is a high-pressure injection filling method, it is possible to achieve net-shape properties, but a challenge is that the magnetic properties are low due to the influence of residual carbon in the binder resin.
[0004] In response to this, the present inventors have developed and proposed a "Pressless Process (PLP)" (see Patent Document 3). In this method, instead of transporting a powder compression molded body made using a magnetic field die press method to a sintering furnace, fine magnet alloy powder densely packed in a filling container (hereinafter referred to as "mold") is oriented in a magnetic field, and the mold is then transported to the sintering furnace. Thin plate magnets are produced by filling a mold with a shallow, large-area dish-shaped cavity with magnet alloy powder, oriented it, and then sintering it. In the conventional pressing method, it is necessary to produce a powder compression molded body having sufficient strength for transportation to the subsequent sintering step, and thus it has been difficult to produce a highly oriented thin-plate shaped green compact by the pressing method. In contrast, in the PLP method, by transporting the powder orientation molded body together with the mold, thin-plate shaped sintered magnets can now be directly produced industrially.
[0005] Further, a "New-PLP method = NPLP method", which is a further improvement of the above "PLP method", has also been proposed by the inventors of the present application (see Patent Document 4). In this NPLP method, an oriented filled molded body of magnet alloy fine powder that is filled into a mold at an appropriate density and oriented in a magnetic field is molded, then the outer wall member of the mold is removed, and the oriented filled molded body is moved to a sintering base plate and carried into a sintering furnace to produce a sintered body. For example, when producing thin-plate magnets by the NPLP method, the cavity in the mold is divided into narrow cavities by a plurality of partition plates, and the narrow cavities partitioned by the partition plates are filled with magnet alloy powder. Thereafter, the mold is capped, a magnetic field is applied to orient the magnet alloy powder to form a plate-shaped oriented filled molded body sandwiched between the partition plates. Thereafter, when transferring to the sintering base plate, the outer wall of the mold is removed, and only the laminate in which the plate-shaped oriented filled molded bodies and the partition plates formed inside the mold are alternately laminated is left on the sintering base plate. Then, the laminate composed of the oriented filled molded bodies and the partition plates left on this sintering base plate is heated in a sintering furnace, and finally, by removing the partition plates, a plurality of thin-plate shaped sintered magnets are produced. Molds used for the production of sintered magnets are made of materials that require a certain level of precision, but when repeatedly exposed to high sintering temperatures of 1000°C or higher, the molds are consumed. Thus, the PLP method had the problem of high mold costs, whereas in the case of the NPLP method, the mold is not placed inside the sintering furnace, so the mold cost problem is resolved.
[0006] As described above, the PLP method and NPLP method employ a dry molding process in which magnetic alloy powder is filled into a mold and a magnetic field is applied to the filled molded body. However, handling fine powder is extremely difficult, and a challenge remains in ensuring that the magnetic alloy powder is uniformly and evenly filled into the mold in a productively stable manner. Specifically, variations in filling can lead to warping or partial shrinkage of the sintered magnets during the sintering process, resulting in variations in the dimensions of the sintered magnets.
[0007] To address the problems associated with the PLP and NPLP methods, Patent Document 5 discloses a wet process in which a slurry is prepared by mixing magnetic alloy powder and a dispersion medium, the slurry is filled into a mold, and a magnetic field is applied in that state. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Special Publication No. 61-34242 [Patent Document 2] Japanese Patent Application Publication No. 9-289127 [Patent Document 3] Patent No. 4391897 [Patent Document 4] Patent No. 6280137 [Patent Document 5] Japanese Patent Publication No. 2015-225880 [Overview of the Initiative] [Problems that the invention aims to solve]
[0009] However, the slurry described in Patent Document 5 is allowed to stand (for example, for 1 hour) to allow the alloy powder to settle densely, and at that time, a supernatant of the dispersion medium is generated. Thus, in order to make the powder uniform in the mold, standing is necessary to allow the alloy powder to settle, which is undesirable from a production standpoint. Also, since the alloy powder and solvent separate during standing, the slurry described in Patent Document 5 requires a process of uniform mixing before use. Furthermore, the manufacturing method in Patent Document 5 has a dispersion medium removal step in which the supernatant of the slurry is removed after filling the mold and before orientation, resulting in a large loss of dispersion medium. In this way, the manufacturing method using the slurry in Patent Document 5 results in a complicated production process. In addition, the manufacturing method in Patent Document 5 removes the dispersion medium while the slurry is filled in the mold and is also dried, so there is a high risk of dispersion medium remaining in the mold. Such residual dispersion medium chemically reacts with the neodymium alloy powder during sintering and remains as an impurity in the sintered body. More specifically, during sintering, oxygen (O), carbon (C), and nitrogen (N) react with rare earth elements (R) such as Nd, inhibiting the formation of Nd-rich grain boundary phases in NdFeB sintered magnets.
[0010] The present invention has been made in view of the above problems, and aims to provide a neodymium alloy powder slurry preferably used in a method for manufacturing NdFeB sintered magnets, and a method for manufacturing NdFeB sintered magnets using the slurry. [Means for solving the problem]
[0011] The present inventors conducted extensive and intensive studies to solve the above problems, and as a result, by mixing a neodymium alloy powder having a surfactant adsorbed on the surface thereof and an organic solvent in a predetermined amount, a highly viscous slurry (or a highly viscous solid content) in which the neodymium alloy powder and the organic solvent are stably compatible with each other could be formed. The inventors have found that by filling a mold with this slurry, the neodymium alloy powder can be stably and uniformly filled into the mold without uneven distribution. This is considered to be because the neodymium alloy and the organic solvent are compatible with each other as a solid content via the surfactant chemically adsorbed on the surface of the neodymium alloy powder, and the neodymium alloy powder in the slurry is given a degree of freedom sufficient for uniform filling. Furthermore, the present inventors have found that by using this slurry, an NdFeB sintered magnet in which residual carbon, residual oxygen and residual nitrogen are suppressed to the same levels as in the dry process can be produced despite the use of an organic solvent, and the present invention has been completed.
[0012] A first aspect of the neodymium alloy powder slurry of the present invention is a neodymium alloy powder slurry comprising a neodymium alloy powder having a surfactant adsorbed on the surface thereof and an organic solvent, wherein the content of the organic solvent is 5 to 30 parts by weight relative to 100 parts by weight of the neodymium alloy powder, and the sedimentation degree represented by the following formulas (1) and (2) is 90% or more. Sedimentation degree 直後 =(H B / H A )×100(%) Formula (1) Sedimentation degree 7日後 =(H C / H A )×100(%) Formula (2) Here, H A represents the height of the slurry measured immediately (10 minutes) after being placed in the container, H B represents the height of the solid content measured immediately (10 minutes) after being placed in the container, and H C represents the height of the solid content measured after being left to stand at room temperature for 7 days. In the first aspect of the neodymium alloy powder slurry of the present invention, it is preferable that the sedimentation degree represented by the formulas (1) and (2) is 95% or more.
[0013] A second aspect of the neodymium alloy powder slurry of the present invention is a neodymium alloy powder slurry comprising neodymium alloy powder on which a surfactant is adsorbed on the surface and an organic solvent, characterized in that the content of the organic solvent is 5 to 30 parts by weight per 100 parts by weight of the neodymium alloy powder, and the entire amount of the organic solvent is retained in the neodymium alloy powder.
[0014] A third aspect of the neodymium alloy powder slurry of the present invention is a neodymium alloy powder slurry comprising neodymium alloy powder on which a surfactant is adsorbed on the surface and an organic solvent, wherein the content of the organic solvent is 5 to 30 parts by weight per 100 parts by weight of the neodymium alloy powder, and the shape retention rate of the slurry-filled molded body 3 hours after preparation is 95% or more and the weight change rate is 15% or less compared to immediately after molding (10 minutes) of the slurry-filled molded body prepared by filling a mold with the slurry.
[0015] In the first, second, or third embodiment of the neodymium alloy powder slurry of the present invention, it is preferable that the surfactant is a fatty acid methyl ester having 3 to 13 carbon atoms. In the first, second, or third embodiment of the neodymium alloy powder slurry of the present invention, it is preferable that the organic solvent is a hydrocarbon compound having 5 to 12 carbon atoms. In the first, second, or third embodiment of the neodymium alloy powder slurry of the present invention, it is preferable that the organic solvent is at least one selected from pentane, hexane, heptane, octane, nonane, decane, undecane, and dodecane.
[0016] The present invention provides a method for manufacturing an NdFeB sintered magnet, comprising: a molding step of filling a mold with any of the neodymium alloy powder slurry described above to produce a slurry-filled molded body; an orientation step of applying a magnetic field to the slurry-filled molded body in the mold to produce an oriented slurry-filled molded body; a solvent removal step of removing the oriented slurry-filled molded body from the mold and removing the organic solvent from the oriented slurry-filled molded body to produce an oriented slurry-filled molded body; and a sintering step of sintering the oriented slurry-filled molded body to produce an NdFeB sintered magnet. The present invention relates to a method for manufacturing an NdFeB sintered magnet, wherein it is preferable that the NdFeB sintered magnet does not have a processing degradation layer. The present invention relates to a method for manufacturing an NdFeB sintered magnet, wherein it is preferable that 10% or less of the entire surface of the NdFeB sintered magnet is a processing degradation layer. In the present invention, a method for manufacturing an NdFeB sintered magnet, the orientation step is preferably a step in which an AC pulsed magnetic field is applied to the slurry-filled molded body in the mold, and then a DC pulsed magnetic field is applied to generate an oriented slurry-filled molded body. The present invention relates to a method for manufacturing an NdFeB sintered magnet, wherein it is preferable that the residual carbon content in the NdFeB sintered magnet is 1500 ppm or less, the residual oxygen content is 1000 ppm or less, and the residual nitrogen content is 1000 ppm or less. [Effects of the Invention]
[0017] The effects of the present invention are as follows: (1) The neodymium alloy powder slurry of the present invention is a paste-like (viscous) slurry in which neodymium alloy powder and organic solvent are stably compatible. Therefore, when filled into a mold, the neodymium alloy powder can be stably and uniformly filled into the mold without bias, and when a magnetic field is applied to the slurry-filled molded body, the degree of orientation is high. (2) The neodymium alloy powder slurry of the present invention maintains the shape of the slurry-filled molded body after filling the mold, making it easy to handle from orientation to removal from the mold and sintering. Furthermore, since the organic solvent only needs to be removed after the orientation slurry-filled molded body is formed, the production process can be simplified. Moreover, since the organic solvent can be removed after removal from the mold, the organic solvent removal rate is high. (3) The neodymium alloy powder slurry of the present invention has little organic solvent loss because there is almost no organic solvent separated from the neodymium alloy powder on which the surfactant has been adsorbed on the surface. (4) The neodymium alloy powder slurry of the present invention is stable in a state in which an organic solvent is affinity to the surface of the neodymium alloy powder on which a surfactant is adsorbed. Therefore, quality control is easy and it is easy to handle in the production process of NdFeB sintered magnets. In other words, by using the neodymium alloy powder slurry of the present invention, thin, small NdFeB sintered magnets can be produced with high quality and efficiency using the Near Net Shape Manufacturing Process (NNSMP). [Brief explanation of the drawing]
[0018] [Figure 1] This is a schematic diagram showing each step of the manufacturing method of the present invention. [Modes for carrying out the invention]
[0019] [Neodymium alloy powder slurry] The neodymium alloy powder slurry of the present invention is a paste containing neodymium alloy powder with a surfactant adsorbed on its surface and an organic solvent. Preferably, the neodymium alloy powder slurry of the present invention is substantially free of binder resin. Particularly preferred is a slurry consisting of neodymium alloy powder with a surfactant adsorbed on its surface and an organic solvent, or a slurry consisting of neodymium alloy powder with a surfactant adsorbed on its surface, a surfactant, and an organic solvent. The neodymium alloy powder slurry of the present invention can be manufactured, for example, by kneading neodymium alloy powder and a surfactant to adsorb the surfactant onto the surface of the neodymium alloy powder, and then mixing in an organic solvent. The surfactant may also be added and adsorbed during the grinding process in the manufacturing of the neodymium alloy powder.
[0020] [Neodymium alloy powder] Neodymium alloy powder is prepared by preparing a neodymium alloy (NdFeB-based alloy) made by the ingot method or strip casting method, followed by hydrogen pulverization, and then pulverizing it in an inert gas atmosphere using a pulverizer (e.g., a jet mill). As mentioned above, it is preferable to add a surfactant during pulverization and produce the powder with the surfactant adsorbed onto the surface.
[0021] NdFeB alloys are not composed solely of Nd, Fe, and B elements. Nd represents rare earth elements including Y and Sc, specifically Y, Sc, La, Ce, Pr, Nd, Eu, Gd, Tb, Dy, Ho, Yb, and Lu, and represents one or more of these. Preferably, it is mainly composed of Nd, Pr, Dy, and Tb, and particularly mainly composed of Nd (70 atomic percent or more, preferably 75 atomic percent or more, particularly 80 atomic percent or more, and 100 atomic percent or less of the rare earth elements). It is preferable that the rare earth elements make up 10 to 15 atomic percent of the total alloy, particularly 12 to 15 atomic percent.
[0022] B is preferably 3 to 15 atomic percent of the total alloy, and more preferably 4 to 8 atomic percent. In addition, one or more elements selected from Al, Cu, Zn, In, Si, P, S, Ti, V, Cr, Mn, Ni, Ga, Ge, Zr, Nb, Mo, Pd, Ag, Cd, Sn, Sb, Hf, Ta, and W may be contained in the total alloy in an amount of 0 to 11 atomic percent, particularly 0.1 to 5 atomic percent. The remainder consists of Fe and unavoidable impurities such as C, N, and O, but it is preferable that Fe makes up 50 atomic percent or more of the total alloy, and more preferably 65 atomic percent or more. It is also acceptable to substitute a portion of the Fe, for example, 0 to 40 atomic percent of Fe, and more preferably 0 to 15 atomic percent, with Co.
[0023] Examples of particle sizes for neodymium alloy powder include an average particle size D50 of 1 μm or more and 10 μm or less. The preferred lower limit for the average particle size D50 of neodymium alloy powder is 1.5 μm or more, 2.0 μm or more, and especially 2.5 μm or more. On the other hand, the preferred upper limit for the average particle size D50 of neodymium alloy powder is 8 μm or less, 6 μm or less, and especially 5 μm or less. For example, the specific gravity of neodymium alloy is 7.0 g / cm³. 3 More than 8.0g / cm 3 The following are some examples: The preferred lower limit for the specific gravity of neodymium alloy is 7.3 g / cm³. 3 In particular, 7.4 g / cm³ 3 In summary, the preferred upper limit is 7.7 g / cm³. 3 The following, in particular, is 7.6 g / cm³. 3 The following applies:
[0024] [Surfactants] Examples of surfactants include those with a boiling point of 50°C or higher and less than 300°C (liquids). The preferred lower limit of the boiling point of a surfactant is 100°C or higher, particularly 200°C or higher, and the preferred upper limit is 280°C or lower, particularly 270°C or lower. Examples of surfactants include fatty acid methyl esters, metal soaps with 6 to 20 carbon atoms, fatty acid esters, and fatty acid amides, with fatty acid methyl esters having 3 to 13 carbon atoms being preferred. Examples of fatty acid methyl esters having 3 to 13 carbon atoms include methyl laurate, methyl acetate, methyl propionate, methyl butyrate, methyl valerate, and methyl caproate. In neodymium alloy powder, the surfactant content per 100 parts by weight of neodymium alloy can be, for example, 0.01 parts by weight or more and 0.30 parts by weight or less. The preferred lower limit for the surfactant content per 100 parts by weight of neodymium alloy is 0.05 parts by weight or more, particularly 0.10 parts by weight or more, and the preferred upper limit is 0.25 parts by weight or less, particularly 0.20 parts by weight or less. If the surfactant content per 100 parts by weight of neodymium alloy is less than 0.01 parts by weight, it becomes difficult to secure a sufficient organic solvent compatible with the neodymium alloy powder, making it difficult to uniformly fill the mold with the neodymium alloy powder, and also making it difficult for the slurry-filled molded body to orient when a magnetic field is applied. If the surfactant content per 100 parts by weight of neodymium alloy is greater than 0.30 parts by weight, the residual carbon content of the NdFeB sintered magnet increases.
[0025] [Organic solvents] Examples of organic solvents include those with a boiling point of 30°C or higher and 300°C or lower. The preferred lower limit of the boiling point of the organic solvent is 50°C or higher, particularly 60°C or higher, and the preferred upper limit of the boiling point is 250°C or lower, 200°C or lower, more preferably 180°C or lower, particularly 160°C or lower. The boiling point of the organic solvent is lower than the boiling point of the surfactant mentioned above, preferably 100°C or more lower, and particularly 150°C or more lower. Preferred organic solvents include hydrocarbon compounds, specifically those with 5 to 12 carbon atoms. For example, at least one selected from pentane, hexane, heptane, octane, nonane, decane, undecane, and dodecane is used. The content of the organic solvent per 100 parts by weight of neodymium alloy powder with adsorbed surfactant can be, for example, 5 parts by weight or more and 30 parts by weight or less. The preferred lower limit of the organic solvent content per 100 parts by weight of neodymium alloy powder is 6 parts by weight or more, particularly 7 parts by weight or more, the preferred upper limit is 25 parts by weight or less, more preferably 20 parts by weight or less, and particularly preferably 15 parts by weight or less. If the organic solvent content per 100 parts by weight of neodymium alloy powder is less than 5 parts by weight, clumps are likely to form, making it difficult to stably and uniformly fill the mold with neodymium alloy powder during production. If the organic solvent content per 100 parts by weight of neodymium alloy powder is greater than 30 parts by weight, the slurry (especially the solid content in the slurry) becomes soft, and the shape retention rate of the slurry-filled molded body after filling the mold decreases. In addition, the organic solvent separated from the neodymium alloy powder becomes more prominent, the loss of organic solvent is noticeable, and the quality of the slurry tends to deteriorate when stored.
[0026] [Physical properties of slurry 1] The neodymium alloy powder slurry of the present invention preferably has a settling degree of 90% or more, as represented by the following formulas (1) and (2). Degree of subsidence 直後 =( H B / H A )×100(%) Formula (1) Degree of subsidence 7日後 =( H C / H A )×100(%) Formula (2) H A H is the height of the slurry measured immediately after it is placed in the container (10 minutes). B H is the height of the solids measured immediately after placing it in the container (10 minutes). c This indicates the height of the solid content measured after standing at room temperature for 7 days.
[0027] To elaborate, H A H is the height of the slurry (or the height of the supernatant liquid, if present) measured immediately after (10 minutes) when a slurry containing 20g of neodymium alloy powder is placed into a container with an inner diameter of 10mm and a height of 105mm (a test tube with a capacity of 12ml). BH is the height of the solid content immediately after (10 minutes). C This is the height of the solid content measured after the mixture has been left to stand at room temperature for 7 days after being added to the room. This sedimentation degree measures the affinity between neodymium alloy powder and organic solvent. A sedimentation degree of 100% means that the entire amount of organic solvent is retained by the neodymium alloy powder, or that all of the mixed organic solvent is compatible with the neodymium alloy powder and there is no separated organic solvent. A sedimentation degree of 100% can also be confirmed, for example, by pouring the slurry into any container, tilting it at a 45-degree angle, and visually checking that no separated liquid is visible. The neodymium alloy powder slurry of the present invention has a sedimentation degree according to formula (1). 直後 It is preferable that it is 90% or more, more preferably 95% or more, even more preferably 97% or more, particularly 99% or more, and most preferably 100%. 直後 When the organic solvent content is 90% or higher, the organic solvent is compatible with the surface of the neodymium alloy powder, enabling uniform filling of the neodymium alloy powder into the mold. Furthermore, a high degree of orientation can be achieved when a magnetic field is applied to the slurry-filled molded body using the neodymium alloy powder. In addition, because the amount of separated organic solvent is small, the loss of organic solvent can be reduced, resulting in high production efficiency. Moreover, the amount of residual carbon due to residual organic solvent can be reduced when forming an NdFeB sintered magnet. The neodymium alloy powder slurry of the present invention has a sedimentation degree according to formula (2). 7日後 It is preferable that it is 90% or more, more preferably 95% or more, even more preferably 97% or more, particularly 99% or more, and most preferably 100%. 7日後 When the content is 95% or higher, the neodymium alloy powder slurry can be stored for a long period of time, which is preferable for the production of NdFeB sintered magnets.
[0028] "Physical Properties of Slurries 2" The neodymium alloy powder slurry of the present invention is characterized by, for example, a slurry-filled molded body that retains its shape for 3 hours after preparation, with a weight change rate of 15% or less, compared to the shape retained immediately after molding (10 minutes) of the slurry-filled molded body. In detail, neodymium alloy powder slurry is filled to the brim into a mold with a diameter of 11.8 mm and a thickness of 12.4 mm using a spatula or similar tool, and the slurry-filled molded body is removed from the mold within 10 minutes. The shape retention rate is calculated from the slurry-filled molded body after molding (10 minutes) and the slurry-filled molded body after standing at room temperature for 3 hours using the following equations (3) to (5). The weight change rate is also calculated using equation (6). "Shape retention rate" = (Shape retention rate of diameter + Shape retention rate of thickness) / 2 Equation (3) "Shape retention rate of diameter" = "1 - (Diameter)" (3h) -diameter (10min) ) / diameter (10min) ”×100 Formula (4) "Shape retention rate of thickness" = "1 - (thickness)" (3h) - thickness (10min) ) / thickness (10min) ”×100 Formula (5) "Rate of weight change" = "(mass (10min) -mass (3h) ) / mass (10min) ”×100 Formula (6) Examples of diameter shape retention rates include 90% or more, preferably 95% or more, more preferably 97% or more, particularly 98% or more, and most preferably 100%. Examples of thickness shape retention rates include 90% or more, preferably 95% or more, more preferably 97% or more, particularly 98% or more, and most preferably 100%. Examples of shape retention rates include 95% or more, preferably 97% or more, more preferably 98% or more, particularly 99% or more, and most preferably 100%. For example, the weight change rate may be 15% or less, and preferably 10% or less. When the shape retention rate of the neodymium alloy powder slurry is 95% or more and the weight change rate is 15% or less, the following method for manufacturing NdFeB sintered magnets according to the present invention allows for the production of high-quality NdFeB sintered magnets with high production efficiency without complicating the post-removal process from the mold.
[0029] Next, the method for manufacturing the NdFeB sintered magnet of the present invention is described. As shown in Figure 1, this manufacturing method comprises a molding step, an orientation step, a solvent removal step, and a sintering step.
[0030] "Molding process" The molding process involves filling a mold with the neodymium alloy powder slurry of the present invention to produce a slurry-filled molded body. Neodymium alloy powder slurry can be filled using its own weight without applying significant pressure (e.g., 10 kg / cm³). 2 Preferably 1 kg / cm³ 2 (See below). For example, the material can be filled into the mold using a spatula or other spoon-like tool, or by pushing it out with a syringe. Alternatively, the material can be filled while applying vibrations such as ultrasound. After filling, the mold can be gently pressed with a lid or the like. Examples of the bulk density of the alloy powder in the slurry-filled molded body include 2.4 g / cc or more and 4.4 g / cc or less. The lower limit of this bulk density is 2.6 g / cc or more, particularly 2.7 g / cc or more, and the preferred upper limit is 4.0 g / cc or less, particularly 3.8 g / cc or less.
[0031] "Orientation process" The orientation process involves applying a magnetic field to the slurry-filled molded body within the mold to orient the neodymium alloy powder in the slurry-filled molded body, thereby obtaining an oriented slurry-filled molded body. In particular, the mold is sealed with a lid or the like to prevent the organic solvent in the slurry-filled molded body from evaporating, and then the magnetic field is applied. A magnetic field can be applied to the molded body by a static magnetic field using an electromagnet or a pulsed magnetic field using an air-core coil. The waveform of the pulsed current can be a DC pulse waveform, an AC attenuated waveform, or a combination of both DC and AC pulse waveforms. Specifically, an AC pulsed magnetic field may be applied to the slurry-filled molded body at least once (preferably 1 to 3 times), and then a DC pulsed magnetic field may be applied. By applying an AC pulsed magnetic field in this way, the magnetic bonding and friction between the slurry-filled molded body and the molded fine powder can be broken (AC crushing), and the orientation by the subsequent application of a DC pulsed magnetic field can be enhanced. Alternatively, a high magnetic field can be generated by passing a large current through a high-temperature superconducting air-core coil. In this case, short-duration current changes are difficult, so it is desirable to apply the magnetic field for a period of 1 second or more but less than 10 seconds. Furthermore, applying a strong magnetic field allows the crystal axes of the particles constituting the powder to be aligned in one direction, thereby improving the magnetic properties after sintering. Therefore, the strength of the applied magnetic field should be 1 Tesla or more, preferably 3 Tesla or more, and particularly 4 Tesla or more. Nd2Fe of neodymium alloy powder after application of magnetic field 14 The degree of orientation of the tetragonal compound in the C-axis direction (easy magnetization direction) is 90% or higher, preferably 93% or higher, and particularly 95% or higher.
[0032] "Solvent removal process" The solvent removal process involves removing the oriented slurry-filled molded body from the mold and removing the organic solvent to produce the oriented slurry-filled molded body. This solvent removal process involves removing the organic solvent at a predetermined temperature, or removing both the organic solvent and the surfactant at a predetermined temperature. Removing the organic solvent from the oriented slurry-filled molded body can be achieved, for example, by maintaining the molded body in an environment above the boiling point of the organic solvent (preferably 20°C or higher above the boiling point). A preferred holding time is 0.5 hours to 10 hours, particularly 1 hour to 5 hours. It is also preferable to maintain the temperature at the above-mentioned temperature for the predetermined time while evacuating the system. In the solvent removal process, by removing the organic solvent, or the organic solvent and surfactant, from the molded body filled with the oriented slurry after removing it from the mold, the amount of organic solvent, or the organic solvent and surfactant remaining in the molded body can be minimized, and impurities resulting from the reaction of the organic solvent, etc., with the neodymium alloy powder during sintering can be reduced. Specifically, impurities that are generated by the reaction of residual oxygen (O), carbon (C), nitrogen (N), and rare earth elements (R) such as Nd, and that inhibit the formation of the Nd-rich grain boundary phase in the NdFeB sintered magnet can be minimized.
[0033] "Sintering process" The sintering process is the process of sintering an oriented and filled molded body. For example, the oriented and filled molded body is placed on a sintering base plate and then sintered in a sintering furnace. The sintering temperature and time are determined appropriately based on the alloy's composition and particle size, but the typical sintering temperature for neodymium alloy powder is around 900°C to 1100°C, and the typical sintering time, including the heating time, is around 10 to 40 hours. Furthermore, the obtained sintered magnet may be subjected to heat treatment under an inert gas atmosphere or a vacuum atmosphere in order to improve its magnetic properties. The heat treatment is preferably carried out at 350°C or higher for 0.5 hours or more and 30 hours or less. In particular, it is preferable to perform a primary heat treatment at 750°C or higher and 1000°C or lower for 0.5 hours or more and 30 hours or less, followed by a secondary heat treatment at 480°C or higher and 700°C or lower for 0.5 hours or more and 30 hours or less after rapid cooling. It is preferable to rapidly cool after the secondary heat treatment.
[0034] NdFeB sintered magnets manufactured by the present invention's method for manufacturing NdFeB sintered magnets are covered with an oxide film (a surface layer containing a large amount of Nd) formed on the surface during sintering. Preferably, this surface layer remains on 90% or more of the entire surface (particularly 95% or more), and especially preferably, the surface layer remains on the entire surface. After the sintering process, minimal finishing work (e.g., removal of burrs) may be performed so that 10% or less of the entire surface (particularly 5% or less) becomes a processed degradation layer (a layer where the surface layer has been removed).
[0035] The amount of residual carbon in the NdFeB sintered magnet is 1500 ppm or less, preferably 1300 ppm or less, and particularly 1200 ppm or less. While a lower residual carbon content is preferable, achieving less than 10 ppm is not practical. The amount of residual oxygen in the NdFeB sintered magnet is 1000 ppm or less, preferably 900 ppm or less, and particularly 800 ppm or less. While a lower residual oxygen level is preferable, achieving a level below 10 ppm is not practical. The amount of residual nitrogen in the NdFeB sintered magnet is 1000 ppm or less, preferably 800 ppm or less, and particularly 500 ppm or less. While a lower residual nitrogen amount is preferable, achieving a level below 10 ppm is not practical. The oxygen and carbon content in this Nd-Fe-B sintered magnet can be analyzed by infrared gas absorption spectroscopy. [Examples]
[0036] "Preparation of neodymium alloy powder" Hydrogen was absorbed into a strip-cast alloy and then hydrogen-dispersed to obtain crude neodymium alloy powder for NdFeB sintered magnets with the composition shown in Table 1. 0.07 parts by weight of methyl laurate per 100 parts by weight of alloy was added to the crude neodymium alloy powder, and the mixture was stirred and mixed in a mixer to adsorb the surfactant. The powder was then pulverized using a nitrogen gas jet mill to produce neodymium alloy powder for NdFeB sintered magnets. The particle size of this powder was measured by laser diffraction and scattering, and the average particle size D50 was 3.0 μm. Furthermore, methyl laurate was added to this powder in a ratio of 0.07 parts by weight per 100 parts by weight of alloy, and the mixture was stirred and mixed in a mixer to adsorb the surfactant. This resulted in neodymium alloy powder with 0.14 parts by weight of methyl laurate adsorbed on the surface per 100 parts by weight of neodymium alloy. [Table 1]
[0037] "Slurry preparation" Under an inert gas atmosphere, 100 parts by weight of neodymium alloy powder prepared in a 20 mL glass container was mixed with octane (organic solvent) in the proportions shown in Table 2, and the mixture was kneaded for 10 minutes in a mini test tube mixer MVM-10 to obtain alloy powder slurries (Examples 1-7, Comparative Examples 1 and 2). The slurries were then evaluated using the method described later. The evaluation results are also shown in Table 2. Furthermore, the volume concentrations of alloy powder and organic solvent in the slurry were calculated using the following equations (7) to (10) based on the bulk density shown in Table 2. The weight of each slurry was then calculated by multiplying each volume concentration by its respective specific gravity. Table 2 shows the proportion of octane when the alloy powder is 100 parts by weight. Volume concentration of alloy powder = bulk density of alloy powder in slurry / true density (7.55) Equation (7) Volume concentration of organic solvent = 1 - Volume concentration of alloy powder in slurry (Equation 8) Weight of alloy powder = Volume concentration of alloy powder in slurry × True density (7.55) Equation (9) Weight of organic solvent = Volume concentration of organic solvent in slurry × Specific gravity of organic solvent Equation (10)
[0038] [Table 2]
[0039] "Separation of solvents" The alloy powder slurries obtained in the examples and comparative examples were placed in 10 mm diameter test tubes, with 20 g of alloy powder used for each slurry. These test tubes were left standing at room temperature, and after a predetermined time, the presence or absence of solvent separation was evaluated by tilting the test tubes at a 45° angle to check for separation of the organic solvent. We evaluated the results as follows: "○" when no separation of organic solvents was observed, and "×" when separation of organic solvents was observed.
[0040] "Degree of subsidence" The neodymium alloy powder slurries obtained in the examples and comparative examples were placed into test tubes with a diameter of 10 mm and a height of 105 mm. The amount of slurry added was 20 g of neodymium alloy powder. The height H of the slurry was measured immediately after adding the slurry (10 minutes). A(If there is a supernatant, the height of the supernatant) and the height of the solids immediately after addition (10 minutes) H B The following was measured: The height of the solid content H was measured after the slurry was added and left to stand at room temperature for 7 days. C The following values were measured. Using these values, the degree of sedimentation is expressed by the following formulas (1) and (2). 直後 , degree of subsidence 7日後 The result was calculated. Degree of subsidence 直後 =( H B / H A )×100(%) Formula (1) Degree of subsidence 7日後 =( H C / H A )×100(%) Formula (2)
[0041] "Dischargeability" Approximately 15 ml of the neodymium alloy powder slurry from the examples and comparative examples was filled into a 5 ml Luer-tip syringe, and the slurry was dispensed by manually pushing the plunger. The dispensing rate at that time was calculated using the following formula (11). Discharge rate = (Amount dispensed / Amount filled) × 100% Equation (11) Discharge rates were evaluated as follows: 60-100% was rated "○", 30-60% as "△", and 0-30% as "×".
[0042] "Fillability" The neodymium alloy powder slurries of the examples and comparative examples were filled to the brim into molds with a diameter of 11.8 mm and a height of 12.4 mm using a spatula. After filling the molds (for example, within 10 minutes), the slurry-filled molded bodies were removed from the molds and their shape and appearance were evaluated. We evaluated the results as follows: "○" when no change in shape was observed, and "×" when a change in shape was observed.
[0043] "Moldability" The neodymium alloy powder slurries of the examples and comparative examples were filled to the brim of a mold measuring 11.8 mm in diameter and 12.4 mm in height using a spatula. After filling the mold (for example, within 10 minutes), the slurry-filled molded body was removed from the mold and the shape retention rate was calculated. The shape retention rate was calculated based on equations (3) to (5) below, as the difference between the slurry-filled molded body immediately after molding (10 minutes) in a mold with a diameter of 11.8 mm and a height of 12.4 mm, and the slurry-filled molded body after standing at room temperature for 3 hours. The weight change rate was also calculated based on equation (6) below. "Shape retention rate" = (Shape retention rate of diameter + Shape retention rate of thickness) / 2 Equation (3) "Shape retention rate of diameter" = "1 - (Diameter)" (3h) -diameter (10min) ) / diameter (10min) ”×100 Formula (4) "Shape retention rate of thickness" = "1 - (thickness)" (3h) - thickness (10min) ) / thickness (10min) ”×100 Formula (5) "Rate of weight change" = "(mass (10min) -mass (3h) ) / mass (10min) ”×100 Formula (6)
[0044] As shown in Table 2, neodymium alloy powder slurries containing 5 parts by weight or more of organic solvent per 100 parts by weight of neodymium alloy powder (Examples 1-7, Comparative Example 2) exhibited good discharge properties. This discharge property confirmed that the neodymium alloy powder slurries of Examples 1-7 and Comparative Example 2 had a higher degree of freedom for the neodymium alloy powder in the slurry compared to the neodymium alloy powder slurry of Comparative Example 1, allowing for uniform filling of the neodymium alloy powder into the mold. Furthermore, neodymium alloy powders containing 30 parts by weight or less of organic solvent per 100 parts by weight of neodymium alloy powder (Examples 1-7, Comparative Example 1) showed a sedimentation degree of 90% or more, indicating that the amount of organic solvent separated from the neodymium alloy powder was reduced. However, as in the neodymium alloy slurry of Comparative Example 2, when the proportion of organic solvent was 40 parts by weight or more per 100 parts by weight of neodymium alloy powder, separation of the organic solvent became significant. This is thought to be because the organic solvent that was compatible with the surface of the neodymium alloy powder became saturated. Furthermore, in the neodymium alloy powder of the examples, the neodymium alloy slurries of Examples 1 to 6, in which the proportion of organic solvent was 20 parts by weight or less per 100 parts by weight of neodymium alloy powder, not only separated the organic solvent but also had good packing properties (initial shape) and were able to maintain a shape retention rate of 95% or more. Moreover, the neodymium alloy slurries of Examples 1 to 4, in which the proportion of organic solvent was 16 parts by weight or less per 100 parts by weight of neodymium alloy powder, were able to retain the entire amount of organic solvent in the neodymium alloy powder and were also able to maintain a shape retention rate of 100%.
[0045] Thus, the neodymium alloy slurries of Examples 1 to 7 produced high-quality slurry-filled molded bodies with uniformly packed powder, minimizing organic solvent loss due to the small amount of separated organic solvent. Furthermore, it was confirmed that the filling properties and shape retention of the slurry-filled molded bodies could be controlled by adjusting the proportion of organic solvent. As a result, handling after removal from the mold was simple, and subsequent solvent removal and sintering processes could be carried out with high precision. Therefore, it was found that small, thin, net-shape NdFeB sintered magnets could be produced efficiently and with high quality. Furthermore, it was found that the neodymium alloy slurry used in the example maintained a high degree of sedimentation and thus maintained its quality even after being left to stand at room temperature for 7 days.
[0046] "Other Examples" Neodymium alloy powder slurries were prepared in the same manner as in Example 1, except that different organic solvents were used for formulations shown in Tables 3 to 6. Solvent separation and sedimentation were then evaluated in the same manner.
[0047] [Table 3]
[0048] [Table 4]
[0049] [Table 5]
[0050] [Table 6]
[0051] The neodymium alloy powder slurries of Examples 8-35 were found to minimize organic solvent loss and stably produce high-quality slurry-filled molded products, similar to the neodymium alloy powder slurries of Examples 1-7. Furthermore, it was confirmed that the filling properties and shape retention rate could be controlled by adjusting the proportion of organic solvent. It was also found that the degree of sedimentation could be maintained at a high level even after standing at room temperature for 7 days, thus maintaining quality. Therefore, it was found that the neodymium alloy powder slurries of Examples 8-35 can also be used to efficiently produce thin, plate-shaped NdFeB sintered magnets in net shape with high quality.
[0052] "Manufacturing of NdFeB sintered magnets" Next, three neodymium alloy powder slurries with the formulation of Example 4 were prepared, and NdFeB sintered magnets of Examples 36-38 were fabricated using these. Specifically, each slurry was filled into a mold with a diameter of 11.8 mm and a height of 12.4 mm using a plastic cylinder, a lid plate was attached to the top surface of the mold with screws, and a 4 Tesla pulsed magnetic field was applied perpendicular to the partition plate to form an oriented-filled molded body. The oriented-filled molded body was placed on a carbon base plate and moved into a sintering furnace. After evacuating the entire sintering furnace with a rotary pump, the temperature was raised to 200°C at a heating rate of 3°C / min. After reaching 200°C, the temperature was maintained for 3 hours while evacuating with a turbomolecular pump to remove the solvent from the oriented-filled molded body. After evacuating the entire sintering furnace with a turbomolecular pump, the temperature was raised to 500°C at a heating rate of 3°C / min, and then to 1000°C at a rate of 2°C / min. After holding at that temperature for 2 hours, heating was stopped and the furnace was allowed to cool to room temperature. The cylindrical sintered body was carefully removed from the sintering furnace along with the carbon base plate.
[0053] "Manufacturing of NdFeB sintered magnets" Next, three neodymium alloy powder slurries with the formulation of Example 4 were prepared, and NdFeB sintered magnets of Examples 39-41 were fabricated using these. Specifically, each slurry was filled into a mold with a diameter of 11.8 mm and a height of 12.4 mm using a plastic cylinder, a lid plate was attached to the top surface of the mold with screws, and a 4 Tesla AC pulsed magnetic field was applied twice perpendicular to the partition plate (two AC crushing cycles), followed by one DC pulsed magnetic field to form an oriented filled molded body. The oriented filled molded body was placed on a carbon base plate and moved into a sintering furnace. After evacuating the entire sintering furnace with a rotary pump, the temperature was raised to 200°C at a heating rate of 3°C / min. After reaching 200°C, the temperature was maintained for 3 hours while evacuating with a turbomolecular pump to remove the solvent from the oriented filled molded body. After evacuating the entire sintering furnace with a turbomolecular pump, the temperature was raised to 500°C at a heating rate of 3°C / min, and then to 1000°C at a rate of 2°C / min. After holding at that temperature for 2 hours, heating was stopped and the furnace was allowed to cool to room temperature. The cylindrical sintered body was carefully removed from the sintering furnace along with the carbon base plate.
[0054] Furthermore, NdFeB sintered magnets of Comparative Examples 3-5 were prepared by dry molding using neodymium alloy powders 1-3 and orientation by applying a DC pulsed magnetic field, as well as NdFeB sintered magnets of Comparative Examples 6-8 were prepared by dry molding using neodymium alloy powders 1-3, AC crushing, and then orientation by applying a DC pulsed magnetic field. Specifically, neodymium alloy powder was filled into a mold with a diameter of 11.8 mm and a height of 12.4 mm, a lid plate was attached to the top surface of the mold with screws, a 4 Tesla pulsed magnetic field was applied perpendicular to the partition plate, or a 4 Tesla AC pulsed magnetic field was applied twice perpendicular to the partition plate (AC crushing twice), followed by a DC pulsed magnetic field was applied once to form an oriented filled molded body, which was then placed on a carbon base plate and moved into a sintering furnace. The temperature was raised to 500°C at a heating rate of 3°C / min, and then raised to 1000°C at a heating rate of 2°C / min. After maintaining that temperature for two hours, the heating was stopped and the material was cooled to room temperature in the furnace. The cylindrical sintered body was then carefully removed from the sintering furnace along with the carbon base plate.
[0055] Table 7 shows the shape and sintering density of the NdFeB sintered magnets for Examples 36-41 and Comparative Examples 3-8. The shape was measured using calipers, and the sintering density was measured using the Archimedes method with an analytical balance AUW320 (manufactured by Shimadzu Corporation).
[0056] [Table 7]
[0057] As shown in Table 7, the NdFeB sintered magnets of the examples had a slightly lower sintering density than the NdFeB sintered magnets of the comparative examples, but the variation in external dimensions was small, confirming that they were filled stably and uniformly.
[0058] Next, the magnetic properties of the NdFeB sintered magnets of Examples 36-41 and Comparative Examples 3-8 were measured using a magnetic property measuring device (BH curve tracer pulse type PHB-1000, manufactured by Nippon Denji Sokki Co., Ltd.). The results are shown in Table 8. Note that "Examples" 直平均 " is the average value of Examples 36-38, which were oriented by applying only a DC pulsed magnetic field, and "Example 交平均 " is the average value of Examples 39-41, in which AC disintegration was followed by orientation by applying a DC pulsed magnetic field. Also, "Comparative Example" 直平均 " is the average value of Comparative Examples 3 to 5, which were oriented by applying only a DC pulsed magnetic field, and "Comparative Example 交平均 This value represents the average of Comparative Examples 6-8, which were oriented after AC disintegration by applying a DC pulsed magnetic field.
[0059] [Table 8]
[0060] Examples 36-38 (Examples) 直平均 When comparing the NdFeB sintered magnet of Example 3 to the NdFeB sintered magnets of Comparative Examples 3 to 5, 直平均The values for residual magnetic flux density (Br), coercivity (Hcj), maximum energy product (BHmax), degree of orientation (Br / Bs), and angularity (Hk / Hcj), which indicates the shape of the JH curve of the demagnetization curve, were higher in the latter case. In particular, the angular magnetic field (Hk) and angularity (Hk / HcJ) were higher in the example. 直平均 This one improved. On the other hand, Examples 39-41 (Examples 交平均 ) NdFeB sintered magnet and Comparative Examples 6-8 (Comparative Examples) 交平均 Compared with the NdFeB sintered magnet of the example, 交平均 In this case, the values for residual magnetic flux density (Br) and coercivity (Hcj) decreased slightly, while the values for maximum energy product (BHmax), degree of orientation (Br / Bs), and prismaticity (Hk / Hcj) increased. Furthermore, in the AC-disintegrated sample, the prismaticity (Hk / Hcj) was also high, as in the example. 交平均 This one improved. From this, it was found that using the slurry of the present invention increases the maximum energy product (BHmax), degree of orientation (Br / Bs), and prismaticity (Hk / Hcj). In particular, the prismaticity was 90% or higher in all sintered magnets, indicating high magnetic performance. This is thought to be because the movement of neodymium alloy powder during orientation is promoted when manufacturing NdFeB sintered magnets using the slurry of the present invention compared to the dry method. Furthermore, by performing AC crushing, the magnetic properties of both the examples and comparative examples were improved, except for the coercivity (Hcj). This is thought to be because using the slurry of the present invention and performing AC crushing further promoted the rotation of the neodymium alloy powder during orientation.
[0061] Next, the residual carbon content (combustion-infrared absorption method), residual oxygen content (inert gas fusion-infrared absorption method and thermal conductivity method), and residual nitrogen content (inert gas fusion-infrared absorption method and thermal conductivity method) of the NdFeB sintered magnets of Example 38 and Comparative Example 3 were measured. The results are shown in Table 9.
[0062] [Table 9]
[0063] The residual carbon, residual oxygen, and residual nitrogen content of the NdFeB sintered magnets produced by the manufacturing method of the present invention were comparable to those of the NdFeB sintered magnets produced by the dry method in Comparative Example 3. Specifically, the residual carbon content of Example 38 was slightly higher than that of Comparative Example 3, but the residual oxygen and residual nitrogen content were lower than those of Comparative Example 3. Thus, it was found that the NdFeB sintered magnet of Example 38 could suppress impurities such as residual carbon content to the same level as sintered magnets produced by the dry method, and that magnetic properties other than prismaticity could be produced at the same level as sintered magnets produced by the dry method. In particular, prismaticity was superior to that of sintered magnets produced by the dry method.
Claims
1. A neodymium alloy powder slurry containing neodymium alloy powder with a surfactant adsorbed on its surface and an organic solvent, The content of the organic solvent is 5 to 30 parts by weight per 100 parts by weight of the neodymium alloy powder. The degree of sedimentation, as expressed by the following formulas (1) and (2), is 90% or more. Neodymium alloy powder slurry. Degree of subsidence 直後 = (H B / H A )×100(%) Formula (1) Degree of subsidence 7日後 = (H C / H A )×100(%) Formula (2) (H A represents the height of the slurry measured immediately (10 minutes) after being placed in the container, H B represents the height of the solid content measured immediately (10 minutes) after being placed in the container, H C represents the height of the solid content measured after being left to stand at room temperature for 7 days.)
2. The degree of settlement expressed by the above formulas (1) and (2) is 95% or more. The neodymium alloy powder slurry according to claim 1.
3. The surfactant is a fatty acid methyl ester having 3 to 13 carbon atoms. The neodymium alloy powder slurry according to claim 1.
4. The aforementioned organic solvent is a hydrocarbon compound having 5 to 12 carbon atoms. The neodymium alloy powder slurry according to claim 1.
5. The organic solvent is at least one selected from pentane, hexane, heptane, octane, nonane, decane, undecane, and dodecane. The neodymium alloy powder slurry according to claim 4.
6. A molding step of filling a mold with a neodymium alloy powder slurry according to any one of claims 1 to 5 to produce a slurry-filled molded body, An orientation step in which a magnetic field is applied to the slurry-filled molded body in the mold to generate an oriented slurry-filled molded body, The process involves removing the oriented slurry-filled molded body from the mold, removing the organic solvent, and generating an oriented slurry-filled molded body; A sintering step to produce an NdFeB sintered magnet by sintering the oriented filled molded body, Having, A method for manufacturing NdFeB sintered magnets.
7. The NdFeB sintered magnet does not have a processing degradation layer. A method for manufacturing an NdFeB sintered magnet according to claim 6.
8. Less than 10% of the entire surface of the NdFeB sintered magnet is a processing degradation layer. A method for manufacturing an NdFeB sintered magnet according to claim 6.
9. The orientation step is a process of applying an AC pulsed magnetic field to the slurry-filled molded body in the mold, and then applying a DC pulsed magnetic field to generate an oriented slurry-filled molded body. A method for manufacturing an NdFeB sintered magnet according to claim 6.
10. The NdFeB sintered magnet contains 1500 ppm or less of residual carbon, 1000 ppm or less of residual oxygen, and 1000 ppm or less of residual nitrogen. A method for manufacturing an NdFeB sintered magnet according to claim 6.
11. A neodymium alloy powder slurry containing neodymium alloy powder with a surfactant adsorbed on its surface and an organic solvent, The content of the organic solvent is 5 to 30 parts by weight per 100 parts by weight of the neodymium alloy powder. The entire amount of the organic solvent is held in the neodymium alloy powder. Neodymium alloy powder slurry.
12. A neodymium alloy powder slurry containing neodymium alloy powder with a surfactant adsorbed on its surface and an organic solvent, The content of the organic solvent is 5 to 30 parts by weight per 100 parts by weight of the neodymium alloy powder. The shape retention rate of the slurry-filled molded body after 3 hours of production is 95% or more, and the weight change rate is 15% or less, compared to the shape retention rate immediately after molding (10 minutes) of the slurry-filled molded body. Neodymium alloy powder slurry.
Citation Information
Patent Citations
Method for weaving twistless non-sized fabric
JP1986034242A
Seat control device for vehicle
JP1987080137A
Manufacture of rare earth permanent magnet, and the rare earth permanent magnet
JP1997289127A
Sintered magnet manufacturing method
JP2015225880A
Manufacturing method and manufacturing device for magnetically anisotropic rare earth sintered magnet
JP4391897B2